The Effect of Ethanol Extract of Cogon Grass Root (Imperata cylindrica) to Estrus Cycle and Metabolite Profile in Female Mice - Robianto, Sondi; Syamsunarno, Mas Rizky Adipurna Anngun; Lubis, Alkaustariyah; Priscilia, Madeleine; Anggraeni, Neni; Ghozali, M.; Ritongga, Mulyanusa; Widyastuti, Rini (Jurnal Veteriner, 2019)
The use of herbs as contraception has become the focus of current contraceptive development.. In the previous study, the extract ethanol of cogon grass roots ( Imperata cylindrica ) has the effect of decreasing sperm production and changing metabolite profiles in male mice. However, the effect of this Indonesian well-known herb is still indefinite in female.The purpose of this study was to investigate the effect of ethanol extract of cogon grass roots to the fertility of female mice. The study was conducted at Animal Laboratory of Faculty of Medicine and Central laboratory Universitas Padjadjaran from November to December 2017. Mice were given ethanol extract of cogon grass roots 90 and 115 mg/kg body weight per oral. After three weeks, vaginal cytology was observed and metabolite profiles were measured. The results showed a shortening of the estrus phase in 90 and 115 mg/kg treatment group. However, the level of glucose and cholesterol in serum were not different among groups. This study indicated the extract ethanol of cogon grass roots has potential effect as contraceptive agent and the effect is independent from metabolite profiles. Keywords: Cogon Grass, Imperata cylindrica, Estrus Cycle Phase, Metabolite Profile